Fag, faglighed og fagordbøger - Balsgart, Karin (HERMES - Journal of Language and Communication in Business, 1993)
This paper argues that one of the reasons that existing bilingual (Danish -> English) LSP dictionaries are unsatisfactory is that insufficient emphasis is attached to the question of defining and delimiting the subject-matter covered, in respect of both the overall selection of entries and the choice and application of field labels. More detailed grammatical considerations are of no real importance in remedying this situation because there is no such thing as a special LSP grammar. An interdisciplinary approach, on the other hand, would seem to offer good prospects, always providing that the linguistic insight is not confined to lexicographic theory and principles but extends to intimate knowledge of both languages. A relatively narrow definition of potential users and uses would also seem beneficial. A number of so-called "business", "technical" and "specialised" dictionaries are reviewed in substantiation of this argument.